Expansion of a single transposable element family is associated with genome-size increase and radiation in the genus Hydra - Wong, Wai Yee; Kuhn, Anne; Holstein, Thomas W. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Transposable elements are one of the major contributors to genome-size differences in metazoans. Despite this, relatively little is known about the evolutionary patterns of element expansions and the element families involved. Here we report a broad genomic sampling within the genus Hydra, a freshwater cnidarian at the focal point of diverse research in regeneration, symbiosis, biogeography, and aging. We find that the genome of Hydra is the result of an expansion event involving long interspersed nuclear elements and in particular a single family of the chicken repeat 1 (CR1) class. This expansion is unique to a subgroup of the genus Hydra, the brown hydras, and is absent in the green hydra, which has a repeat landscape similar to that of other cnidarians. These features of the genome make Hydra attractive for studies of transposon-driven genome expansions and speciation.
Gesehen am 28.04.2020